(untitled) (Quinto Sol, 2013)
Legal protection of accumulated and transgenerational developed knowledge by indigenous peoples and local communities, especially those associated with the properties, uses and characteristics of biological diversity, raises some issues and uncertainties. The Intellectual Property Legal Regimen in force, which establishes the basis for the protection of an individual author’s work, and the Patent System are not able to protect collective traditional knowledge. The aim of this paper is to discuss not only the limitations that exist in the Argentine legal system to protect them adequately, but also the challenges involved, including from practical problems of registration to deeper issues related to the nature of traditional knowledge and the difficulties to design effective mechanisms to respect the worldview, culture and customary law of the peoples involved and able to prevent their use for commercial applications.